2013
DOI: 10.1038/srep02932
|View full text |Cite|
|
Sign up to set email alerts
|

CDK5 is essential for TGF-β1-induced epithelial-mesenchymal transition and breast cancer progression

Abstract: Epithelial-mesenchymal transition is a change of cellular plasticity critical for embryonic development and tumor metastasis. CDK5 is a proline-directed serine/threonine kinase playing important roles in cancer progression. Here we show that CDK5 is commonly overexpressed and significantly correlated with several poor prognostic parameters of breast cancer. We found that CDK5 participated in TGF-β1-induced EMT. In MCF10A, TGF-β1 upregulated the CDK5 and p35 expression, and CDK5 knockdown inhibited TGF-β1-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 54 publications
(83 reference statements)
3
112
0
1
Order By: Relevance
“…It has also been documented that different CDKs may contribute specifically to different tumor types in humans (17,18). CDK5, an atypical CDK that was previously considered to function in processes unrelated to cell-cycle regulation, has been shown to play a fundamental role in several kinds of carcinomas including breast, lung, prostate, multiple myeloma, and pancreatic cancers (39)(40)(41)(42)(43). However, the potential role of CDK5 in gastric cancer has never been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been documented that different CDKs may contribute specifically to different tumor types in humans (17,18). CDK5, an atypical CDK that was previously considered to function in processes unrelated to cell-cycle regulation, has been shown to play a fundamental role in several kinds of carcinomas including breast, lung, prostate, multiple myeloma, and pancreatic cancers (39)(40)(41)(42)(43). However, the potential role of CDK5 in gastric cancer has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that CDK5 in fact plays an inhibitory role in gastric tumorigenesis. The kinase activity of CDK5 has been thought to mediate carcinogensis of certain nongastric cancer types (39)(40)(41)(42)(43). Our previous studies indicated that nuclear CDK5 can function as a cell-cycle suppressor in the nervous system (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Cdk5-Nrf2 signaling seems to be ubiquitous, in view of its occurrence in neurons besides astrocytes. Nrf2 is also elevated in cancer cells, 13,42,43 hence it is tempting to speculate that Cdk5 -which contributes to cancer progression 44 -would sustain Nrf2-mediated antioxidant activity and survival of rapidly proliferating cells.…”
Section: Discussionmentioning
confidence: 99%
“…CDK5 has previously been shown to be overexpressed in patients with breast cancer, pancreatic cancer, medullary thyroid carcinoma, prostate cancer, lung cancer, and glioblastoma, 81,82 and is an autophagy inducer in neurons in in vitro models of Parkinson disease. 83 We found that stratification of expression of our gene set by the alteration status of molecular changes previously implicated in breast cancer (Table S5) revealed increased mRNA levels of ATG5 and FOXO3 in KRAS-amplified BRCA patients.…”
Section: Clear Cell Renal Carcinomamentioning
confidence: 99%